2004
DOI: 10.1097/01.alc.0000122764.60626.af
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Related Olfactory Cues Activate the Nucleus Accumbens and Ventral Tegmental Area in High‐Risk Drinkers: Preliminary Findings

Abstract: Alcoholic olfactory cues may invoke the dopaminergic mesocorticolimbic system to a greater degree than nonalcoholic odors and could be effective tools in exploring the role of the dopamine system in susceptibility to alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 48 publications
11
91
1
1
Order By: Relevance
“…Interestingly, we did not observe differential activity in the VS corresponding to alcohol vs control cues as previously reported by other groups (eg Kareken et al, 2004); instead, we found increased DS/caudate activity. Increased activation for alcohol compared with the control cue was also found in the thalamus, an area that has also been implicated in cue elicited craving (Modell et al, 1990;George et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, we did not observe differential activity in the VS corresponding to alcohol vs control cues as previously reported by other groups (eg Kareken et al, 2004); instead, we found increased DS/caudate activity. Increased activation for alcohol compared with the control cue was also found in the thalamus, an area that has also been implicated in cue elicited craving (Modell et al, 1990;George et al, 2001).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, a priori ROI analyses indicated that gustatory alcohol cues elicited activation in many of the structures that have been previously implicated in the development and expression of craving for a variety of drugs of abuse including the VTA/SN (Kareken et al, 2004), OFC (Hermann et al, 2006;Myrick et al, 2004), and medial PFC (Kalivas and Volkow, 2005;Myrick et al, 2004;Park et al, in press). Interestingly, we did not observe differential activity in the VS corresponding to alcohol vs control cues as previously reported by other groups (eg Kareken et al, 2004); instead, we found increased DS/caudate activity.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Moreover, EtOH-associated cues that activate the nucleus accumbens/striatum (1,(24)(25)(26)(27)(28) can significantly facilitate EtOH seeking that accompanies relapse in human alcoholics (1, 24-26, 42, 43). Thus, it is intriguing that AGS3 up-regulation, which may drive EtOH seeking during abstinence, is restricted to the NAcore (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced PR responding during abstinence described above was reinforced by EtOH delivery; thus, acute EtOH effects, rather than the cuing effects of stimuli previously associated with EtOH, may have driven EtOH seeking. Because conditioned cues can increase craving and prime relapse in alcoholics (1,(24)(25)(26)(27)(28), we examined whether EtOH-associated cues could maintain responding under the PR when a clear Plexiglas barrier blocked access to the EtOH-containing dipper cup (''3 wk barrier''). Bedding, treated as above, provided an EtOH odor cue.…”
Section: Motivation To Seek Etoh Is Enhanced During Etoh Abstinencementioning
confidence: 99%